Use of constructed wetland systems in the treatment of black waters in rural areas (Research, Society and Development, 2020)
The lack of planning in the area of basic sanitation is a relevant factor for the criticality of public health, quality of life, environmental degradation and the country's development. This situation is aggravated in rural areas, due to the high cost of conventional systems installing and maintaining. In this context, the constructed wetland systems (CW) emerge as a promising alternative, with its implementation and maintenance relatively simple, the possibility of using accessible materials and landscape elements. In view of such perspectives, the present research aimed to evaluate the treatment of black waters through the constructed wetland systems for a residence in a rural area in the Piracicaba / MG region. The plant species used was Typha domingensis (Taboa) and analyzes of BOD, total nitrogen, phosphorus, turbidity, pH and total solids were performed. As a result, it was observed that the cattail showed adequate adaptation to the system. The CW provided satisfactory efficiency in reducing the evaluated parameters, with emphasis on turbidity, which reached 95.5% removal, indicating a high rate of removal of suspended solids. The removal of BOD was also significant, with a mean of 78.2%. Phosphorus reduction reached 84%, while nitrogen was reduced by 41%, on average. The system also showed an efficiency of 88.6% in the removal of total solids and the pH remained close to neutrality. Given the results, it appears that the release of the sanitary effluent from the analyzed residence comply with the conditions required by Brazilian environmental legislation and corroborates the feasibility of implementing the constructed wetland systems in rural areas.